THE INFLUENCE OF STANDARD OPERATING PROCEDURES (SOP), IMPLEMENTATION OF ACCRUAL-BASED ACCOUNTING SYSTEMS, ORGANIZATIONAL CITIZEN BEHAVIOR ON THE QUALITY OF FINANCIAL STATEMENTS - Waspodo, Lego; Primasari, Dona (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2023)
This study examines the factors that influence the quality of financial statements. The main objective of this study is to analyze whether the Standard Operating Procedure, the implementation of accrual-based accounting systems and Organization citizen behavior are factors that influence the quality of financial statements. This type of research uses hypothesis testing, which is research that explains phenomena in the form of relationships between variables. The research sample consisted of the Head of Service / Agency, Treasurer and financial staff at the Regional Work Unit of Lampung province with a total of 97 samples. This study uses Statistical Product and Service Solution (SPSS) analysis version 25.00 with multiple linear regression programs. The results of the study accept all hypotheses from the three hypotheses proposed. The Standard Operating Procedure (SOP) variable has a positive effect on the quality of financial statements. The implementation of accrual-based accounting systems proved to have a positive effect on the quality of financial statements and the organizational citizen behavior variable proved to have a positive effect on the quality of financial statements.